Friday

April 18, 2014

April 18, 2014

Posted by **Matt** on Tuesday, October 25, 2011 at 11:46pm.

(a)

3x1 − 2x2 = −1

4x1 + 5x2 = 3

7x1 + 3x2 = 2

(b)

2x1 + 2x3 =1

3x1 − x2 + 4 x3 = 7

6x1 + x2 − x3 = 0

(c)

x1 + 2x2 − x4 + x5 =1

3x2 + x3 − x5 = 2

x3 + 7x4 =1

(d)

x1 =1

x2 = 2

x3 = 3

- Math -
**Steve**, Wednesday, October 26, 2011 at 1:51pmWhat's the problem? You have all the coefficients and constants. Just write them down as an array. Just copy what you have, throwing all the variable names away, aligning the numbers in columns.

For example, #c is

1 2 0 -1 1 | 1

0 3 1 0 -1 | 2

0 0 1 7 0 | 1

**Related Questions**

Augmented Matrix - Perform row operations on the augmented matrix as far as ...

Augmented Matrix - can someone please help me solve this question? I tried so ...

Math - Find the value of c to make the following augmented matrix corresponding ...

Augmented Matrix - can someone please help me solve this question? I tried so ...

Algebra help! - Please help and I would appreciate an explanation as to how you ...

Algebra help! - 1.) Solve the system by triangularizing the augmented matrix and...

New Age Math - Given the initial augmented matrix -1 1 2 0 2 -1 -3 0 2 -2 -4 0 ...

Algebra - I have a few questions I need help with! 1. Solve the system by ...

College Math - Given the initial augmented matrix 1 -1 0 2 3 -2 -2 3 -2 2 1 -3 ...

Algebra help needed please!! - I have a few questions I need help with! 1. Solve...